2022
DOI: 10.1523/jneurosci.1736-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Tilt in Place Microscopy: a Simple, Low-Cost Solution to Image Neural Responses to Body Rotations

Abstract: Animals use information about gravity and other destabilizing forces to balance and navigate through their environment. Measuring how brains respond to these forces requires considerable technical knowledge and/or financial resources. We present a simple alternative—Tilt In Place Microscopy (TIPM), a low-cost and noninvasive way to measure neural activity following rapid changes in body orientation. Here, we used TIPM to study vestibulospinal neurons in larval zebrafish during and immediately after roll tilts.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 60 publications
(96 reference statements)
0
33
0
Order By: Relevance
“…Instead, retrograde tracing studies across chick, zebrafish, frog, and mouse had collectively identified coarse axonal projections – e.g., to spinal or ocular motor circuits – as their primary organizational axis 1820,62 . Here, we used a modern toolkit consisting of: (1) a transgenic line of zebrafish that specifically labels vestibulo-ocular reflex projection neurons 28 , (2) in vivo birthdating 56 early in development, and (3) spatial mapping of tilt responses 54 . These tools allowed us to extend the “axonal projection” model of vestibular brainstem organization to functional channels within an individual vestibular nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Instead, retrograde tracing studies across chick, zebrafish, frog, and mouse had collectively identified coarse axonal projections – e.g., to spinal or ocular motor circuits – as their primary organizational axis 1820,62 . Here, we used a modern toolkit consisting of: (1) a transgenic line of zebrafish that specifically labels vestibulo-ocular reflex projection neurons 28 , (2) in vivo birthdating 56 early in development, and (3) spatial mapping of tilt responses 54 . These tools allowed us to extend the “axonal projection” model of vestibular brainstem organization to functional channels within an individual vestibular nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were performed on 5 dpf larvae (Transgenic lines). Stimulation paradigms were presented as previously reported in 54 and are described again below. Larvae were paralyzed using bath application of 0.8 mg/mL pancuronium bromide (Sigma-Aldrich P1918, St. Louis, MO) for 8-10 minutes.…”
Section: Star Methodsmentioning
confidence: 99%
See 3 more Smart Citations